1969
DOI: 10.1111/j.1600-0765.1969.tb01984.x
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular deepening by the technique of Edlan and Mejchar

Abstract: Deepening of the inferior labial vestibule was undertaken according to the technique of Edlan and Mejchar on 25 patients aged 17–55 years (X =). Observations were made at intervals, the total period ranging from (X =). Mean vestibular depth before operation was 2.24 ± 0.15 and post‐operatively 6.96 ± 0.23, the difference of 4.72 mm. was statistically significant (P < 0.01). Pre‐operatively the gingival state on the labial aspect of the mandibular central incisors showed a mean value of 2.28 ± 0.36 units and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

1975
1975
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…(4) No periodontal dressing was placed to prevent severe postoperative frictional pain as well as heavy scarring and osseous deformation apical to the flap. Following the institution of these modifications, the cited side effects previously observed by the authors and other investigators (Edlan & Mejchar 1967, Wade 1969, Bergenholtz & Hugoson 1973) could be avoided. The subperiostea!…”
Section: Discussionmentioning
confidence: 98%
“…(4) No periodontal dressing was placed to prevent severe postoperative frictional pain as well as heavy scarring and osseous deformation apical to the flap. Following the institution of these modifications, the cited side effects previously observed by the authors and other investigators (Edlan & Mejchar 1967, Wade 1969, Bergenholtz & Hugoson 1973) could be avoided. The subperiostea!…”
Section: Discussionmentioning
confidence: 98%
“…In 1969, Wade reported that adequate width of attached gingiva is a common requirement for root coverage. Hence, vestibular deepening is an effective technique for gaining the width of the attached gingiva and avoiding gingival recession [7].…”
Section: Discussionmentioning
confidence: 99%
“…All these procedures have a common requirement of adequate width of attached gingiva prior to root coverage procedures. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%